COMPARISON OF STUDENT LEARNING OUTCOMES USING COOPERATIVE LEARNING MODEL SNOWBALL THROWING WITH GROUP INVESTIGATION ON THE MAIN MATERIAL OF PLANT TISSUE STRUCTURE IN CLASS XI IPA MAN 1 MEDAN - Irda Wahidah Nst; Nurul Hidayah Nasution (Jurnal Scientia, 2022)
This study aims to determine student learning outcomes using the Snowball Throwing type learning model with the Group Investigation type, and to find out whether there are differences in student learning outcomes using the Snowball Throwing type learning model with the Group Investigation type on the subject matter of Plant Tissue Structure in class XI Science. MAN 1 Medan. The population in this study were all students of class XI at MAN 1 as many as 266 people. While the research sample was taken randomly with a total of 76 students. This type of research is experimental research. Based on the test results of data analysis requirements, it is known that both student learning outcomes data in the Snowball Throwing class and in the Group Investigation type class are declared to be normally distributed and have homogeneous variance. Based on the results of data analysis, it can be seen that there are differences in learning outcomes in the two research classes. Student learning outcomes using the Snowball Throwing type were 82.53 with a standard deviation of 7.84, while student learning outcomes using the Group Investigation type were 75.56 with a standard deviation of 5.99. The difference in learning outcomes in the two research classes was also proven through hypothesis testing using t-test and confidence level = 0.05 where tcount > ttable (4.38 > 1.99), which means in this study Ho is rejected and Ha received. So that it can be stated that there is a significant difference in student learning outcomes who are taught with the Snowball Throwing type cooperative learning model with the Group Investigation type on the subject matter of Plant Tissue Structure in class XI IPA MAN 1 Medan.